Next generation brain health: transforming global research and public health to promote prevention of dementia and reduce its risk in young adult populations - Mc Glinchey, Eimear (My University, 2024)
Efforts to prevent dementia can benefit from precision interventions delivered to the right population at the right time; that is, when the potential to reduce risk is the highest. Young adults (aged 18–39 years) are a neglected population in dementia research and policy making despite being highly exposed to several known modifiable risk factors. The risk and protective factors that have the biggest effect on dementia outcomes in young adulthood, and how these associations differ across regions and groups, still remain unclear. To address these uncertainties, the Next Generation Brain Health team convened a multidisciplinary expert group representing 15 nations across six continents. We identified several high-priority modifiable factors in young adulthood and devised five key recommendations for promoting brain health, ranging from individual to policy levels. Increasing research and policy focus on brain health across the life course, inclusive of younger populations, is the next crucial step in the efforts to prevent dementia at the global level.
PUBLISHED
Keywords: Ageing